An evaluation of the effectiveness of the fourth year career streaming program of San Beda College - Roque, Ricardo R. (Animo Repository, 1996)
The study validates the effectiveness of the San Beda College High School Department Career Streaming Program (CSP) for fourth year students. The subjects were 82 senior students of four career sections namely Business-Commerce, Pre-Law, Pre-Med, and Engineering. Sampling procedure was stratified-purposive. Sampling started with the whole population of seniors reduced to four groups based on career sections. From these sections, 82 students were chosen. The files of these students presented complete information/data pertinent to the study. All statistical tests were done using an alpha level of .05. The t-test results showed that students were not grouped properly, i.e., certain student groups can be categorized in at least two sections. In terms of proficiency in the core subjects, t-test results further showed that expectations were not met--that students of a particular career section would significantly perform better in the core subjects specified for that section. This assumption was true only for the Engineering students. Although it was shown through linear regression analyses that the final ratings can significantly predict the semestral grades, the stepwise multiple regression analyses indicated that only the 3rd year final grades in the core subjects contributed significantly to the variance observed in the semestral grade. As regards students' course preference for college, a matching was found--students' do prefer, and subsequently pass, a course related to their career section. This, however, is reversed in the Pre-Law class. The students' assessment of the effectiveness of the program also proved varied. A content analysis of survey results showed that students were divided--expressing both positive and negative opinions--as to (a) teachers' effectiveness and influence (b) adequacy of resources (c) parental participation in the program (d) effectiveness of the various activities that supplement the program namely congresses, career talks, conferences, etc. and (e) the appropriateness of the grouping done. It was, however, noted that the outcomes were congruous with the intended results/effects based on the program goals and/or objectives. In summary, the objective of assisting students in making career decisions for college and making students apply for and pass courses related to their career field in high school was met.